Glass fiber reinforced acrylic resin composition
The glass fiber-reinforced acrylic resin composition addresses the challenge of maintaining transparency and mechanical strength by using a methacrylic resin with a ring structure, achieving high light transmittance and strength for optical applications.
Patent Information
- Application Number
- JP2021063621
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-04-02
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2041-04-02
AI Technical Summary
Conventional glass fiber-reinforced acrylic resins face challenges in maintaining transparency while achieving mechanical strength and heat resistance, as the introduction of glass fibers often leads to refractive index mismatch and loss of transparency.
A glass fiber-reinforced acrylic resin composition is developed using a methacrylic resin with a ring structure in its main chain, combined with a fibrous glass filler, to reduce refractive index difference and enhance compatibility, resulting in improved mechanical strength, heat resistance, and transparency.
The composition maintains high total light transmittance and mechanical strength, making it suitable for optical applications by minimizing refractive index mismatch and ensuring transparency.
Smart Images

Figure 0007611755000001 
Figure 0007611755000002 
Figure 0007611755000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an acrylic resin composition containing a fibrous glass filler, and a molded article and the like using the same. [Background technology]
[0002] In general, polymethyl methacrylate resin (PMMA) or copolymers mainly composed of methyl methacrylate are used in a wide range of fields such as automobile parts, electrical parts, and displays because of their excellent transparency, surface gloss, mechanical strength, and moldability.
[0003] However, its impact resistance, heat distortion resistance, and molding dimensional stability are not necessarily sufficient, and its linear expansion coefficient is also large, so its use is limited in applications where the actual environmental temperature is high, such as automobile parts, due to its poor shape stability. Since the introduction of a heat-resistant structure to improve heat distortion resistance reduces the impact resistance of the resin, a method of introducing glass fibers has been disclosed as a method of improving impact resistance. (Patent Document 1) On the other hand, when glass fibers are introduced, if the difference in the optical refractive index between the glass fibers and the resin is large, the light transmitted through the resin is refracted randomly, and transparency is often lost. It has been disclosed that by mixing styrene-acrylonitrile copolymers with PMMA, the difference in the optical refractive index between the glass fibers and the resin is reduced, and transparency can be maintained. (Patent Document 2) However, although a high light transmittance can be maintained, a mixture of PMMA and styrene-acrylonitrile copolymers, which have poor compatibility, cannot be made into a mixture with low haze without turbidity, and a clear and transparent molded product cannot be made. In particular, when the proportion of styrene-acrylonitrile copolymer is low, turbidity becomes significant, and in the region with a low refractive index (region close to PMMA), a clear and transparent glass fiber reinforced acrylic resin composition cannot be obtained. In addition, when the proportion of styrene-acrylonitrile copolymer is high, the glass transition temperature indicating heat resistance becomes close to that of styrene-acrylonitrile copolymers, and the heat resistance is poor. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent Publication No. 1-223152 [Patent Document 2] Patent Publication No. 5-331335 Summary of the Invention [Problem to be solved by the invention]
[0005] In the conventional method, when fibrous glass filler is added to improve the mechanical strength of the resin, transparency is lost, which is a serious obstacle to application to optical applications. The objective of the present invention is to provide a glass fiber reinforced acrylic resin composition that has both transparency, mechanical strength, and heat resistance. [Means for solving the problem]
[0006] In view of the above circumstances, the present inventors have conducted extensive research and have completed the present invention. That is, it has been discovered that by employing a resin composition containing a methacrylic resin having a ring structure in the main chain, and preferably further containing a styrene copolymer, it is possible to obtain a glass fiber reinforced acrylic resin composition that reduces the refractive index difference with the fibrous glass filler and achieves both transparency, mechanical strength, and heat resistance. The glass fiber reinforced acrylic resin composition of the present invention maintains a high level of total light transmittance while improving mechanical strength, and is therefore suitable for optical applications.
[0007] The present invention [1] A glass fiber reinforced acrylic resin composition containing a methacrylic resin having a ring structure in the main chain and a fibrous glass filler. [2] The fibrous glass filler of the present invention preferably contains 35 to 100 mass% silicon dioxide (SiO2), 0 to 30 mass% aluminum oxide (Al2O3), 0 to 15 mass% boron oxide (B2O3), and 0 to 65 mass% others (magnesium oxide, zinc oxide, barium oxide, etc.). [3] The fibrous glass filler of the present invention preferably has a primary shape with a fiber diameter of 3 to 25 μm and a fiber length of 0.5 to 10 mm. [4] In the glass fiber reinforced acrylic resin composition of the present invention, the content of the fibrous glass filler is preferably from 2% by mass to 30% by mass. [5] The methacrylic resin of the present invention preferably has one or more ring structures selected from the group consisting of cyclic lactone, glutaric anhydride, glutarimide, maleic anhydride, and maleimide. [6] The glass fiber reinforced acrylic resin composition of the present invention preferably further contains a styrene copolymer, and more preferably the content of the styrene copolymer is 10% by mass or more and 50% by mass or less. Furthermore, the styrene copolymer is more preferably a styrene-acrylonitrile copolymer or a styrene-acrylonitrile-phenylmaleimide copolymer. [7] In the glass fiber-reinforced acrylic resin composition of the present invention, the difference in refractive index between the methacrylic resin and the fibrous glass filler is preferably 0.03 or less, or the difference in refractive index between the resin composition containing the methacrylic resin and a styrene copolymer and the fibrous glass filler is preferably 0.03 or less. [8] It is preferable that a molded article made of the glass fiber reinforced acrylic resin composition of the present invention has a total light transmittance of 80% or more at a thickness of 3 mm in accordance with JIS K7361. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] Hereinafter, the embodiment of the present invention will be described in detail. In the following description, unless otherwise specified, "%" means "% by mass" and "parts" means "parts by mass". In addition, "A to B" indicating a range indicates A or more and B or less.
[0009] [Methacrylic resin with a ring structure in the main chain] The methacrylic resin having a ring structure in the main chain may usually have a methacrylic acid ester unit [a unit (structural unit) derived from a methacrylic acid ester].
[0010] The methacrylic acid ester constituting the methacrylic acid ester unit is not particularly limited, and examples thereof include methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, sec-butyl methacrylate, tert-butyl methacrylate, pentyl methacrylate, amyl methacrylate, isoamyl methacrylate, n-hexyl methacrylate, 2-ethylhexyl methacrylate, heptyl methacrylate, octyl methacrylate, decyl methacrylate, dodecyl methacrylate, pentadecyl methacrylate, hexadecyl methacrylate, heptadecyl methacrylate, Examples of the methacrylate include alkyl aliphatic methacrylates such as octadecyl methacrylate, alicyclic methacrylates such as cyclopropyl methacrylate and cyclobutyl methacrylate, crosslinked cyclic methacrylates such as isobornyl methacrylate, aromatic methacrylates such as phenyl methacrylate and o-tolyl methacrylate, aralkyl methacrylates such as benzyl methacrylate, phenoxyalkyl methacrylates such as phenoxyethyl methacrylate, methacrylates having a hydroxyl group such as 2-hydroxyethyl methacrylate, methacrylates having an alkoxy group, and methacrylates having a glycidyl group.
[0011] The methacrylic acid ester units may be constituted by one type or a combination of two or more types of methacrylic acid ester.
[0012] The methacrylic acid ester units preferably contain at least methacrylic acid alkyl ester units, and more preferably contain at least methacrylate methyl units.
[0013] The methacrylic resin having a ring structure in the main chain may contain units derived from other polymerizable monomers (monomers) other than the (meth)acrylic acid ester units, as necessary. Examples of such other monomers include acrylic acid esters, acid group-containing monomers (methacrylic acid, acrylic acid, etc.), styrene-based monomers [for example, styrene, vinyl toluene, styrenes having substituents (for example, halogen groups, alkoxy groups, alkyl groups, hydroxy groups, etc.) (for example, α-methylstyrene, chlorostyrene, etc.), styrenesulfonic acid or salts thereof, etc.], vinyl esters (for example, vinyl acetate, etc.), unsaturated nitriles (for example, acrylonitrile, methacrylonitrile, etc.), olefin-based monomers (for example, C olefins such as ethylene, propylene, 1-butene, isobutylene, 1-octene, etc.), and the like. 2-10 alkenes), amide group-containing vinyl monomers [for example, (meth)acrylamide, N-substituted (meth)acrylamides (for example, N-alkyl (meth)acrylamides such as N-methyl (meth)acrylamide; N-cycloalkyl (meth)acrylamides such as N-cyclohexyl (meth)acrylamide; N-aryl (meth)acrylamides such as N-phenyl (meth)acrylamide; N-aralkyl (meth)acrylamides such as N-benzyl (meth)acrylamide, etc.)], 2-(hydroxymethyl)acrylic acid esters (for example, alkyl esters such as ethyl 2-(hydroxymethyl)acrylate), etc.
[0014] The other monomers may be one type or two or more types may be combined to form units derived from the other monomers.
[0015] The content of the methacrylic acid ester units in the methacrylic resin having a ring structure in the main chain can be selected, for example, from the range of 10% by mass or more, and may be preferably 30% by mass or more, more preferably 50% by mass or more, 60% by mass or more, 70% by mass or more, etc. [Ring structure] Methacrylic resins having a ring structure in the main chain can impart, improve or enhance various physical properties of the methacrylic resin (e.g., heat resistance, hardness (strength), solvent resistance, surface hardness, oxygen and water vapor barrier properties, optical properties, dimensional stability, shape stability, refractive index, birefringence, etc.) by introducing the ring structure. In addition, the presence of the ring structure improves the dispersibility of the fibrous glass filler. This is thought to be because the presence of the ring structure in the main chain results in heteroatoms being arranged perpendicular to the main chain, improving the affinity or wettability to the acidic surface of the fibrous glass filler.
[0016] Examples of the ring structure include cyclic imide structures such as a maleimide structure and a glutarimide structure, cyclic anhydride structures such as a maleic anhydride structure and a glutaric anhydride structure, cyclic amide structures (e.g., a lactam structure, etc.), and cyclic ester structures such as a lactone ring structure.
[0017] The methacrylic resin having a ring structure in the main chain of the present invention may have one or more ring structures. When the methacrylic resin has two or more ring structures, the two or more ring structures may be ring structures of the same system, such as two or more cyclic imide structures, or may be ring structures of different systems, such as a combination of a cyclic imide structure and a lactone structure.
[0018] Examples of the glutarimide structure and glutaric anhydride structure include a structure represented by the following formula (1).
[0019] [ka]
[0020] (In the formula, R 1 and R 2 are each independently a hydrogen atom or an alkyl group; R 3 is a hydrogen atom or a substituent, and X 1 is an oxygen atom or a nitrogen atom. 1 When is an oxygen atom, n=0, and X 1is a nitrogen atom, n=1.) R in Equation (1) 1 and R 2 In the above, examples of the alkyl group include alkyl groups having 1 to 8 carbon atoms, such as a methyl group, ethyl group, n-propyl group, isopropyl group, n-butyl group, isobutyl group, tert-butyl group, n-pentyl group, isopentyl group, n-hexyl group, isohexyl group, n-heptyl group, isoheptyl group, n-octyl group, and 2-ethylhexyl group.
[0021] R 1 and R 2 is particularly preferably a hydrogen atom or an alkyl group having 1 to 4 carbon atoms.
[0022] R in Equation (1) 3 In the above formula, examples of the substituent include a hydrocarbon group.
[0023] Examples of the hydrocarbon group include an aliphatic group, an alicyclic group, an aromatic group, etc. The hydrocarbon group may further have a substituent such as a halogen.
[0024] R in Equation (1) 3 In the formula, examples of the aliphatic group include alkyl groups having 1 to 10 carbon atoms, such as methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, n-pentyl, isopentyl, n-hexyl, isohexyl, n-heptyl, isoheptyl, n-octyl, and 2-ethylhexyl. Among these alkyl groups, alkyl groups having 1 to 4 carbon atoms, particularly methyl, are preferred.
[0025] R in Equation (1) 3 In the above, examples of the alicyclic group include cycloalkyl groups having 3 to 12 carbon atoms, such as a cyclopropyl group, a cyclobutyl group, a cyclopentyl group, and a cyclohexyl group. Among these cycloalkyl groups, a cycloalkyl group having 3 to 7 carbon atoms, in particular a cyclohexyl group, is preferred.
[0026] R in Equation (1) 3 In the above, examples of the aromatic group include, for example, C 6-20 Examples of aromatic groups having 6 to 20 carbon atoms include aryl groups (for example, phenyl group, o-tolyl group, m-tolyl group, p-tolyl group, 2,3-xylyl group, 2,4-xylyl group, 2,5-xylyl group, 2,6-xylyl group, 3,4-xylyl group, 3,5-xylyl group, 1-naphthyl group, 2-naphthyl group, binaphthyl group, and anthryl group); and aralkyl groups having 7 to 20 carbon atoms, such as benzyl group. Of these aromatic groups, phenyl group and tolyl group are preferred.
[0027] Typically, in formula (1), R 1 and R 2 are each independently a hydrogen atom or a methyl group, R 3 may be an alkyl group having 1 to 10 carbon atoms, a cycloalkyl group having 3 to 12 carbon atoms, or an aromatic group having 6 to 20 carbon atoms, and preferably R 1 and R 2 are each independently a hydrogen atom or a methyl group, R 3 may be an alkyl group having 1 to 4 carbon atoms, a cycloalkyl group having 3 to 7 carbon atoms, an aryl group having 6 to 20 carbon atoms, or an aralkyl group having 7 to 20 carbon atoms, and more preferably, R 1 and R 2 are each independently a hydrogen atom or a methyl group, R 3 is a methyl group, a cyclohexyl group, a phenyl group or a tolyl group, and most preferably R 1 and R 2 are each independently a hydrogen atom or a methyl group, R 3 may be a cyclohexyl group or a phenyl group.
[0028] The ring structure may have one or more types of structures represented by formula (1).
[0029] In particular, when the ring structure has a structure represented by formula (1), a glutarimide structure which is a cyclic non-anhydride structure (i.e., in formula (1), X 1 is a nitrogen atom).
[0030] In addition, the glutaric anhydride structure (i.e., in formula (1), X 1 A ring structure in which is an oxygen atom) may be hydrolyzed or have an increased acid value, which may reduce water resistance or hot water resistance or cause fluctuations in optical properties. Therefore, it may be preferable that the ring structure does not substantially have a glutaric anhydride structure, or contains only a small amount of the glutaric anhydride structure.
[0031] Examples of the maleic anhydride structure and the maleimide structure include a structure represented by the following formula (2).
[0032] [ka]
[0033] (In the formula, R 4 , R 5 are each independently a hydrogen atom or a methyl group, and R 6 is a hydrogen atom or a substituent, and X 2 is an oxygen atom or a nitrogen atom. X 2 When is an oxygen atom, n=0, and X 2 is a nitrogen atom, n=1.) R in Equation (2) 6 In the above formula, examples of the substituent include a hydrocarbon group.
[0034] The hydrocarbon group may be, for example, an aliphatic group {e.g., an alkyl group [e.g., C 1-6 Straight-chain alkyl groups (e.g., methyl, ethyl, etc.), C 1-6 Branched alkyl groups (e.g., isopropyl groups, etc.) 1-6 alkyl group, etc.}, alicyclic groups (e.g., cyclopentyl group, cyclohexyl group, etc. 3-20 cycloalkyl groups, etc.), aromatic groups {e.g., C 6-20 Aromatic groups [e.g., C 7-20 Aralkyl groups (e.g., benzyl groups, etc.), C 6-20aryl group (for example, phenyl group, etc.)}. The hydrocarbon group may further have a substituent such as a halogen.
[0035] X 2 When is an oxygen atom, the ring structure represented by formula (2) becomes a maleic anhydride structure.
[0036] On the other hand, X 2 When is a nitrogen atom, the ring structure represented by formula (2) is a maleimide structure.
[0037] In formula (2), X 2 When is a nitrogen atom, preferably, R 4 and R 5 are each independently a hydrogen atom, R 6 C 3-20 Cycloalkyl group or C 6-20 It may be an aromatic group, more preferably R 4 and R 5 are each independently a hydrogen atom, R 6 may be a cyclohexyl group, a benzyl group or a phenyl group.
[0038] The ring structure may have one or more types of structures represented by formula (2).
[0039] In particular, when the ring structure has a structure represented by formula (2), a maleimide structure which is a cyclic non-anhydride structure (i.e., in formula (2), X 2 is a nitrogen atom).
[0040] In addition, the maleic anhydride structure (i.e., in formula (2), X 2 A ring structure in which is an oxygen atom) may be hydrolyzed or have an increased acid value, which may reduce water resistance or hot water resistance, or may cause fluctuations in optical properties. Therefore, it may be preferable that the ring structure does not substantially have a maleic anhydride structure, or may contain only a small amount of the maleic anhydride structure.
[0041] The lactone ring structure is not particularly limited and may be, for example, a 4- to 8-membered ring, but is preferably a 5- or 6-membered ring, and more preferably a 6-membered ring, due to its excellent stability as a ring structure.
[0042] The lactone ring structure may be, for example, a structure disclosed in JP-A-2004-168882, and examples thereof include a structure represented by the following formula (3).
[0043] [ka]
[0044] (In the formula, R 7 , R 8 and R 9 are each independently a hydrogen atom or a substituent. In the formula (3), examples of the substituent include organic residues such as hydrocarbon groups.
[0045] Examples of the hydrocarbon group include aliphatic groups (e.g., C groups such as methyl, ethyl, and propyl groups). 1-20 C such as alkyl group, ethenyl group, and propenyl group 2-20 unsaturated aliphatic hydrocarbon groups, aromatic groups (e.g., phenyl groups, naphthyl groups, etc.) 6-20 Aromatic hydrocarbon groups, etc.
[0046] The hydrocarbon group may contain an oxygen atom, and one or more hydrogen atoms may be substituted with at least one type of group selected from a hydroxyl group, a carboxyl group, an ether group, and an ester group.
[0047] In formula (3), preferably, R 9 is a hydrogen atom or a methyl group, R 7 and R 8 are each independently a hydrogen atom or C 1-20 More preferably, R 9 is a hydrogen atom or a methyl group, R 7 and R8 may each independently be a hydrogen atom or a methyl group.
[0048] The ring structure may contain one or more types of structures represented by formula (3).
[0049] The lactam ring structure is not particularly limited, and examples thereof include a pyrrolidinone ring structure represented by the following formula (4).
[0050] The pyrrolidinone ring structure has a five-membered amide ring structure (cyclic amide structure) as a basic skeleton. This cyclic amide structure is also a five-membered lactam structure (γ-lactam structure). Having a pyrrolidinone ring structure in the main chain means that at least one atom of the five atoms constituting the basic skeleton of the five-membered pyrrolidinone ring structure, typically three carbon atoms not constituting an amide bond (—N(R)CO—), is located in the main chain of the polymer and constitutes the main chain.
[0051] [ka]
[0052] (In the formula, R 10 ~R 12 are each independently a hydrogen atom or a substituent. R in Equation (4) 10 In the above, the substituents include, for example, a hydrocarbon group or -NHCOR 13 Group(R 13 is a hydrogen atom or a hydrocarbon group).
[0053] R 10 or R 13 Examples of the hydrocarbon group in include an aliphatic group, an alicyclic group, and an aromatic group.
[0054] Examples of the aliphatic group include C 1-18 Alkyl groups (e.g., methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, and other C 1-18Linear or branched alkyl groups, etc.
[0055] Examples of the alicyclic group include C 3-18 Examples of the cycloalkyl group include a cyclopropyl group, a cyclobutyl group, a cyclopentyl group, and a cyclohexyl group.
[0056] Examples of aromatic groups include C 6-20 Aromatic groups [e.g., C 6-20 Aryl groups (e.g., phenyl, tolyl, xylyl, naphthyl, anthryl, etc.), C 7-20 aralkyl groups (for example, benzyl groups, etc.).
[0057] R 10 In particular, hydrogen atom, C 1-18 Straight-chain alkyl groups (eg, methyl groups, etc.) are preferred.
[0058] Also, R 13 In particular, hydrogen atom, C 1-18 A straight chain alkyl group (preferably C 1-12 A straight chain alkyl group, more preferably C 1-4 Straight chain alkyl groups, etc.), C 6-20 Aryl groups (e.g., phenyl groups, etc.), C 3-18 Cycloalkyl groups (preferably C 3-12 Cycloalkyl groups, more preferably C 3-6 Cycloalkyl groups and the like are preferred.
[0059] R in Equation (4) 11 In the above, examples of the substituent include -COOR 14 Group(R 14 is a hydrogen atom or a hydrocarbon group).
[0060] R 14 Examples of the hydrocarbon group in 10 or R 13 Examples of the hydrocarbon groups include those exemplified by
[0061] Also, R 14Particularly preferred embodiments of the invention are also 13 This is the same as the particularly preferred embodiment of the above.
[0062] R in Equation (4) 12 In the above, examples of the substituent include -COR 15 Group(R 15 is a hydrogen atom or a hydrocarbon group).
[0063] R 15 Examples of the hydrocarbon group in 10 or R 13 Examples of the hydrocarbon groups include those exemplified by
[0064] Also, R 15 Particularly preferred embodiments of the invention are also 13 This is the same as the particularly preferred embodiment of the above.
[0065] The ring structure of the methacrylic resin having a ring structure in the main chain may be appropriately selected depending on the desired physical properties (e.g., heat resistance, hardness (strength), solvent resistance, surface hardness, barrier properties against oxygen and water vapor, optical properties, dimensional stability, shape stability, etc.). For example, from the viewpoint of heat resistance, etc., the ring structure may suitably contain a lactone ring structure, a cyclic imide structure (e.g., an N-alkyl substituted maleimide structure, a glutarimide structure, etc.), or a cyclic anhydride structure (e.g., a maleic anhydride structure, a glutaric anhydride structure, etc.).
[0066] From the viewpoint of water resistance and hot water resistance, the ring structure may preferably contain a cyclic non-anhydride structure [for example, a lactone ring structure, or a cyclic imide structure (particularly, a glutarimide structure, or a maleimide structure)].
[0067] Furthermore, from the viewpoints of surface hardness, solvent resistance, barrier properties, optical properties, and the like, the ring structure may suitably contain a lactone ring structure, a glutarimide structure, a glutaric anhydride structure, or the like.
[0068] The content of the ring structure can be selected depending on the application, desired physical properties, and the like, and is not particularly limited. For example, in the methacrylic resin having a ring structure in the main chain, the content can be selected from a range of about 0.1% by mass or more (e.g., 0.5% by mass or more), and may be 1% by mass or more, preferably 3% by mass or more, more preferably 5% by mass or more, or may be 10% by mass or more, 15% by mass or more, 20% by mass or more, etc.
[0069] The content ratio of the ring structure (or its upper limit) is not particularly limited, and may be, for example, 90% by mass or less, 80% by mass or less, 70% by mass or less, 60% by mass or less, 55% by mass or less, 50% by mass or less, 45% by mass or less, 40% by mass or less, 35% by mass or less, etc., in the methacrylic resin having a ring structure in the main chain. In addition, it is also possible to adjust the birefringence by including a ring structure, and it is also possible to obtain, for example, a zero birefringence resin by copolymerizing a unit derived from a polymerizable monomer other than the above-mentioned (meth)acrylic acid ester unit and including a styrene copolymer described later.
[0070] A larger content of the ring structure is preferable in terms of heat resistance, hardness (strength), solvent resistance, surface hardness, dimensional stability, and the like.
[0071] On the other hand, if the content of the ring structure is too high, the resin may become brittle or may lose transparency.
[0072] From this viewpoint, the ring structure may be contained in an appropriate proportion, which is neither too small nor too large.
[0073] Incidentally, these upper and lower limits may be appropriately combined to set an appropriate range (for example, 1 to 70 mass%, 3 to 60 mass%, 5 to 60 mass%, 5 to 50 mass%, etc.) (the same applies below).
[0074] In particular, when the methacrylic resin having a ring structure in its main chain has a glutarimide structure and / or a glutaric anhydride structure, the content of the glutarimide structure and / or the glutaric anhydride structure may be preferably 5 mass% or more, more preferably 10 mass% or more, and even more preferably 15 mass% or more, and may be 90 mass% or less, preferably 60 mass% or less, more preferably 50 mass% or less, and even more preferably 40 mass% or less.
[0075] When the methacrylic resin having a ring structure in its main chain has a maleic anhydride structure and / or a maleimide structure, the content of the maleic anhydride structure and / or the maleimide structure may be, for example, 5 to 90 mass%, preferably 5 to 60 mass%, more preferably 10 to 50 mass%, and further preferably 10 to 30 mass%.
[0076] When the methacrylic resin having a ring structure in the main chain has a lactone ring structure, the content of the lactone ring structure may be, for example, 1 to 80 mass%, preferably 3 to 70 mass%, and more preferably 5 to 60 mass% (for example, 10 to 50 mass%).
[0077] When the methacrylic resin having a ring structure in the main chain has a lactam ring structure, the content of the lactam ring structure may be, for example, about 1 to 80 mass %, preferably about 5 to 70 mass %, and more preferably about 10 to 50 mass %.
[0078] The weight average molecular weight (Mw) of the methacrylic resin having a ring structure in the main chain is not particularly limited, but may be, for example, 10,000 or more (e.g., 10,000 to 1,000,000), preferably 20,000 or more (e.g., 25,000 to 500,000), and more preferably 30,000 or more (e.g., 50,000 to 300,000).
[0079] In addition, the molecular weight distribution (Mw / Mn) of the methacrylic resin having a ring structure in the main chain is not particularly limited, but may be, for example, about 1 to 10 (e.g., 1.1 to 7.0), preferably about 1.2 to 5.0 (e.g., 1.5 to 4.0), or may be about 1.5 to 3.0.
[0080] The molecular weight (and molecular weight distribution) may be measured, for example, using GPC and converted into polystyrene.
[0081] The glass transition temperature (Tg) of the methacrylic resin having a ring structure in the main chain is not particularly limited, but is preferably 115°C or higher, more preferably 116°C or higher, 117°C or higher, 118°C or higher, and 119°C or higher in that order, and more preferably 120°C or higher.
[0082] When the methacrylic resin having a ring structure in the main chain is a copolymer, the form of the copolymerization is not particularly limited, and may be a random copolymer, a block copolymer, an alternating copolymer, a graft copolymer, or the like.
[0083] For example, a methacrylic resin having a ring structure in the main chain can usually be called a copolymer because it has a ring structure, but the manner in which the ring structure is introduced is not particularly limited and can be selected depending on the type of ring structure, etc., and may be introduced randomly, or may be introduced in a block, alternating, graft, or other manner.
[0084] The methacrylic resin having a ring structure in the main chain may be a commercially available product or may be synthesized by a known method.
[0085] For example, an acrylic resin having a glutarimide structure as a ring structure can be obtained by a known method such as a method of imidizing an acrylic resin containing a (meth)acrylic acid ester unit (for example, the methods described in JP-A-2006-309033, JP-A-2006-317560, JP-A-2006-328329, JP-A-2006-328334, JP-A-2006-337491, JP-A-2006-337492, JP-A-2006-337493, JP-A-2007-009182, etc.).
[0086] An acrylic resin having a glutaric anhydride structure can be obtained, for example, by a method of intramolecular dealcoholization reaction between adjacent (meth)acrylic acid ester units and (meth)acrylic acid units (for example, the methods described in JP-A-2006-283013, JP-A-2006-335902, and JP-A-2006-274118).
[0087] The acrylic resin having a maleic anhydride structure or a maleimide structure is, for example, a monomer containing maleic anhydride and / or a maleimide monomer [e.g., maleimide; N-alkylmaleimide (e.g., N-methylmaleimide, N-ethylmaleimide, etc. 1-10 N-alkylmaleimides, N-cycloalkylmaleimides (e.g., cyclohexylmaleimide, etc.) 3-20 cycloalkylmaleimides), N-arylmaleimides (e.g., N-phenylmaleimide, etc. 6-10 N-arylmaleimides, N-aralkylmaleimides (e.g., N-benzylmaleimide, etc. 7-10 The acrylic resin can be obtained by copolymerizing an N-substituted maleimide (such as an aralkylmaleimide) with a monomer constituting an acrylic resin (such as a (meth)acrylic acid ester).
[0088] Acrylic resins having a lactam ring structure can be obtained, for example, by copolymerizing lactam monomers [e.g., N-vinylpyrrolidone monomers (e.g., N-vinylpyrrolidone, N-vinyl-4-butylpyrrolidone, N-vinyl-4-propylpyrrolidone, N-vinyl-4-ethylpyrrolidone, N-vinyl-4-methylpyrrolidone, N-vinyl-4-methyl-5-ethylpyrrolidone, N-vinyl-4-methyl-5-propylpyrrolidone, N-vinyl-5-methyl-5-ethylpyrrolidone, N-vinyl-5-propylpyrrolidone, N-vinyl-5-butylpyrrolidone, etc.), N-vinylcaprolactam monomers (e.g., N-vinylcaprolactam, N-vinyl-6-methylcaprolactam, N-vinyl-6-propylcaprolactam, N-vinyl-7-butylcaprolactam, etc.)] with monomers constituting acrylic resins (e.g., (meth)acrylic acid esters, etc.).
[0089] The acrylic resin composition of the present invention preferably contains at least a methacrylic resin having a ring structure in the main chain, and further contains a styrene copolymer. By containing a styrene copolymer, the refractive index of the resin region can be adjusted, and the transparency of the glass fiber reinforced acrylic resin composition can be improved. In addition, the birefringence of the resin composition containing a methacrylic resin and a styrene copolymer can be adjusted, and for example, a zero birefringence resin can be obtained. Examples of the styrene copolymer include a styrene-methyl methacrylate copolymer, a styrene-acrylonitrile copolymer, an acrylonitrile-butadiene-styrene block copolymer (ABS resin), and an acrylate-styrene-acrylonitrile copolymer (ASA resin), and a styrene-acrylonitrile copolymer or a styrene-acrylonitrile-phenylmaleimide copolymer are particularly preferred. The styrene-acrylonitrile copolymer or the styrene-acrylonitrile-phenylmaleimide copolymer preferably has a styrene / acrylonitrile ratio of 65 to 90% by weight of styrene and 10 to 35% by weight of acrylonitrile, and more preferably 70 to 85% by weight of styrene and 15 to 30% by weight of acrylonitrile. [Other resins] The other resin can be appropriately selected depending on the desired physical properties, etc., and is not particularly limited. It may be a thermoplastic resin, a curable resin, or a combination of these.
[0090] Specific examples of other resins include olefin resins (e.g., polyethylene, polypropylene, ethylene-propylene copolymers, poly(4-methyl-1-pentene), etc.), halogen-based resins (e.g., halogenated vinyl resins such as polyvinyl chloride, polyvinylidene chloride, and polyvinyl chloride), polyester resins (e.g., aromatic polyesters such as polyethylene terephthalate, polybutylene terephthalate, and polyethylene naphthalate), polyamide resins (e.g., aliphatic polyamide resins such as polyamide 6, polyamide 66, and polyamide 610), polyacetal resins, polycarbonate resins, polyphenylene oxide resins, polyphenylene sulfide resins, polyether ether ketone resins, polysulfone resins, polyethersulfone resins, and rubber polymers (e.g., styrene resins (e.g., styrene copolymers such as ABS resin and ASA resin) blended with rubber (polybutadiene rubber, acrylic rubber, etc.)).
[0091] The other resins include acrylic resins (acrylic resins). Examples of the acrylic resins include acrylic resins that do not belong to the category of methacrylic resins having a ring structure in the main chain [or acrylic resins that do not have a ring structure, for example, methacrylic resins having structural units derived from methacrylic acid esters (for example, the above-mentioned exemplified methacrylic acid esters such as methyl methacrylate) (for example, resins having methacrylic acid esters such as polymethyl methacrylate as a polymerization component, resins having methacrylic acid esters such as methyl methacrylate-styrene copolymers and aromatic vinyl compounds as polymerization components), etc.
[0092] The other resins may be used alone or in combination of two or more kinds.
[0093] When the acrylic resin composition of the present invention contains other resins, the content ratio of the other resins in the resin can be selected from the range of, for example, about 90 mass% or less (e.g., 0.1 to 85 mass%) and may be about 80 mass% or less (e.g., 0.5 to 70 mass%), preferably about 60 mass% or less (e.g., 1 to 55 mass%), and may be 50 mass% or less (e.g., 1 to 45 mass%), 40 mass% or less (e.g., 1 to 35 mass%), 30 mass% or less (e.g., 1 to 25 mass%), 20 mass% or less (e.g., 1 to 15 mass%), 10 mass% or less (e.g., 1 to 5 mass%), etc.
[0094] From the viewpoint of efficiently exhibiting the properties of acrylic (optical properties such as transparency, hardness, etc.), even when other resins are contained, it is preferable that the proportion of other resins (especially other non-acrylic resins) is not too large.
[0095] The content of the methacrylic resin having a ring structure in the main chain in the resin can be selected from the range of, for example, 10% by mass or more (e.g., 15 to 100% by mass) and may be 20% by mass or more (e.g., 30% by mass or more), preferably 40% by mass or more (e.g., 45% by mass or more), more preferably 50% by mass or more (e.g., 55% by mass or more), 60% by mass or more (e.g., 65% by mass or more), 70% by mass or more (e.g., 75% by mass or more), or 80% by mass or more (e.g., 85% by mass or more).
[0096] In addition, it is preferable to have a larger amount of methacrylic resin having a ring structure in the main chain, since the properties of acrylic having a ring structure (heat resistance, hardness (strength), solvent resistance, surface hardness, optical properties, dimensional stability, shape stability, etc.) can be easily expressed. [Fiber glass filler] The fibrous glass filler used in the methacrylic resin composition of the present invention can be in any shape, such as roving, chopped strand, middle fiber, glass beads, surfacing mat, chopped strand mat, satin weave, lattice weave, plain weave, open-weave plain weave, twill weave, net, etc., and the types that are preferably used include quartz glass, borosilicate glass, fluorosilicate glass, soda glass, potassium-lime glass, and lead glass. As the fibrous glass filler, E-GF, S-GF, T-GF, etc. (alkali-free glass fiber), C-GF, etc. (alkali-containing glass fiber), etc. are preferably used, and those with a thickness of about 3 to 25 μm and a fiber length of about 0.5 to 10 mm are suitable. When the glass fiber is treated and used, there is no particular restriction on the coupling agent, but silane-based ones are suitable.
[0097] The fibrous glass filler of the present invention preferably contains 35 to 100 mass % of silicon dioxide (SiO2), 0 to 30 mass % of aluminum oxide (Al2O3), 0 to 15 mass % of boron oxide (B2O3), and 0 to 65 mass % of others (magnesium oxide, zinc oxide, barium oxide, etc.). [Glass fiber reinforced methacrylic resin composition] The content of the fibrous glass filler in the glass fiber reinforced methacrylic resin composition of the present invention is preferably from 2% by mass to 30% by mass.
[0098] If the amount of the fibrous glass filler is less than 2% by mass, satisfactory impact resistance and rigidity cannot be obtained, so it is more preferably 3% by mass or more, 4% by mass or more, 5% by mass or more, 6% by mass or more, 7% by mass or more, 8% by mass or more, 9% by mass or more, or 10% by mass or more. If the amount of the fibrous glass filler is more than 30% by mass, molding processability deteriorates, so it is more preferably 29% by mass or less, 28% by mass or less, 27% by mass or less, 26% by mass or less, 25% by mass or less, 24% by mass or less, 23% by mass or less, 22% by mass or less, 21% by mass or less, or 20% by mass or less.
[0099] The glass fiber reinforced methacrylic resin composition of the present invention thus obtained can be molded into a desired shape at a resin temperature of 200 to 300° C., preferably 200 to 280° C., by adding conventional molding aids such as colorants, mold release agents, external lubricants, weather resistance improvers, and antioxidants as necessary. This molding process can be carried out by any method such as injection molding, extrusion molding, or compression molding.
[0100] The term "the refractive index of the resin component containing the methacrylic resin or the methacrylic resin and styrene copolymer is substantially the same as that of the fibrous glass filler" as described in the present invention means that the refractive index matches within a range in which transparency can be confirmed, and it is preferable that the refractive index matches within a range of ±0.03, and more preferably within ranges of ±0.025, 0.02, 0.015, 0.01, and ±0.005, in that order. Various additives may be added to the composition of the present invention as long as the transparency can be maintained. For example, dyes and pigments, heat stabilizers, ultraviolet absorbers, plasticizers, etc. may be added as necessary.
[0101] The glass fiber reinforced methacrylic resin composition of the present invention preferably has a total light transmittance of 80% or more for a molded product having a thickness of 3 mm according to JIS K7361. In addition, the transparency is preferably such that a 3 mm thick molded product is placed as a test piece on graph paper and the scale at 5 mm intervals can be recognized through the test piece. [Uses of glass fiber reinforced methacrylic resin composition] Applications of the glass fiber reinforced methacrylic resin composition include fields requiring transparency, heat resistance and high rigidity, such as optical parts for automobile parts, lighting equipment, office automation equipment and audiovisual equipment. Examples of automotive parts include meter covers around instrument panels, headlamps, taillamps, light guide rods, and front panels of car navigation systems; examples of lighting equipment include light source covers and front panels; and examples of optical parts include front panels and protective covers used in displays. The material can also be used as a modifier for other resins. <Example> The present invention will be described in more detail below by showing examples. However, the scope of the present invention is not limited to these examples. All modifications and variations that do not deviate from the spirit of the present invention are included in the technical scope of the present invention.
[0102] In the following examples, various physical properties were measured and evaluated by the following methods. [Weight average molecular weight (Mw) and molecular weight distribution (Mw / Mn)] The weight average molecular weight and molecular weight distribution of the resin were determined in terms of polystyrene using gel permeation chromatography (GPC) using the following apparatus and conditions:
[0103] System: Tosoh GPC system HLC-8320 Measurement column configuration Guard column: Tosoh, TSKguardcolumn SuperHZ-L Separation column: Tosoh TSKgel SuperHZM-M, 2 columns connected in series Reference column configuration Reference column: Tosoh, TSKgel SuperH-RC Developing solvent: THF (Wako Pure Chemical Industries, special grade) Flow rate of developing solvent: 0.6mL / min Standard sample: TSK standard polystyrene (Tosoh, PS-oligomer kit) Column temperature: 40℃ [Glass transition temperature (Tg)] The glass transition temperature was measured in accordance with the provisions of JIS K7121. Specifically, a differential scanning calorimeter (Rigaku's "Thermo plus EVO DSC-8230") was used to measure the glass transition temperature by the starting point method from a DSC curve obtained by heating about 10 mg of a sample from room temperature to 200°C (heating rate 20°C / min) under a nitrogen gas atmosphere. α-alumina was used as a reference. [Melt flow rate (MFR)] The melt flow rate was measured in accordance with JIS K 7210 B method at a temperature of 230° C. and a load of 3.8 kg (37 N). [Total light transmittance (Tt)] The total light transmittance was measured on a 3 mm thick molded body using a turbidity meter (NDH 5000, manufactured by Nippon Denshoku Industries Co., Ltd.) in accordance with the provisions of JIS K7361. The molded body was produced by drying the obtained pellets at 100°C for 12 hours or more, and then using an injection molding machine (NS40-5A, manufactured by Nissei Plastics Co., Ltd.) at a molding temperature of Tg+105°C, a mold temperature of Tg-40°C, and a mold size of 100 mm x 100 mm x 3 mm thick. [Transparency] Using an injection molding machine (Nissei Plastics, NS40-5A), a molding temperature of Tg+105℃, a mold temperature of Tg-40℃, and a mold size of 100mm x 100mm x 3mm thickness was used to produce a molded body. The molded body was placed on graph paper as a test piece, and the graph paper's scale (1mm intervals, 5mm intervals, 1cm intervals, 5cm intervals) was checked with the naked eye through the test piece to see if it could be recognized; those that could be recognized were marked with an O, and those that could not be recognized were marked with an X. [Three-point bending test] The three-point bending test was performed using Shimadzu Corporation's autograph "AGS-X 1kN" and measuring a 3 mm thick molded body in accordance with the provisions of JIS K7171:2016. (Production Example 1 [Acrylic Resin (A1)]) A reaction vessel equipped with a stirrer, a temperature sensor, a cooling tube, a nitrogen inlet tube, and a dropping pump was charged with 2.6 parts by weight of methyl 2-(hydroxymethyl)acrylate (RHMA), 17.7 parts by weight of methyl methacrylate (MMA), and 47.7 parts by weight of toluene, and the temperature was raised to 105°C while passing nitrogen through.
[0104] As an initial initiator, a solution consisting of 0.44 parts by weight of toluene and 0.12 parts by weight of t-amyl peroxy isononanoate (manufactured by Arkema Yoshitomi Co., Ltd., Luperox (registered trademark) 570) was dropped over 9 minutes, while solution polymerization was performed at 105 ° C. to 110 ° C. Then, 11 minutes later, a solution consisting of 0.56 parts by weight of toluene and 0.15 parts by weight of t-amyl peroxy isononanoate (manufactured by Arkema Yoshitomi Co., Ltd., Luperox (registered trademark) 570) was dropped over 180 minutes as a dropping initiator. In addition, simultaneously with the dropping initiator injection, a solution consisting of 4.0 parts by weight of 2-(hydroxymethyl) methyl acrylate (RHMA) and 26.5 parts by weight of methyl methacrylate (MMA) was dropped over 180 minutes, while solution polymerization was performed at 105 ° C. to 110 ° C., and further aging was performed over 100 minutes.
[0105] To the obtained polymerization solution, a solution consisting of 0.22 parts by weight of toluene and 0.04 parts by weight of stearyl phosphate (Phoslex A-18, manufactured by Sakai Chemical Industry Co., Ltd.) was added as a catalyst for the cyclization condensation reaction (cyclization catalyst), and the cyclization condensation reaction for forming a lactone ring structure was allowed to proceed for 1.5 hours under reflux at approximately 90°C to 110°C.
[0106] Next, the obtained polymerization solution was passed through a multi-tube heat exchanger maintained at 220°C to complete the cyclization condensation reaction, and then introduced into a vent-type screw twin-screw extruder (L / D=52) with a leaf disk-type polymer filter (filtration accuracy 5μm) at the tip at a processing rate of 90 parts by weight / hour in terms of resin amount to devolatilize the polymerization solution. The number of rear vents of the vent-type screw twin-screw extruder used was 1, and the number of fore vents was 4 (referred to as the first, second, third, and fourth vents from the upstream side), the barrel temperature was 220°C, and the degree of vacuum was 13.3 to 400hPa (10 to 300mmHg). During devolatilization, ion-exchanged water was introduced from behind the first and third vents at a rate of 1.3 parts by weight / hour, and a solution of an antioxidant prepared separately was introduced from behind the third vent at a rate of 0.6 parts by weight / hour. As the antioxidant solution, a solution in which 1.0 part by weight of two types of antioxidants (Irganox 1010 manufactured by BASF Japan and Adeka STAB AO-412S manufactured by ADEKA) was dissolved in 30.4 parts by weight of toluene was used.
[0107] The resulting resin pellets (A1) had a weight average molecular weight of 85,000, a molecular weight distribution of 2.1, a glass transition temperature of 123° C., and a melt flow rate of 5.0. (Production Example 2 [Acrylic Resin (A2)]) A reaction vessel equipped with a stirrer, a temperature sensor, a cooling tube, a nitrogen inlet tube, and a dropping pump was charged with 5.1 parts by weight of methyl 2-(hydroxymethyl)acrylate (RHMA), 17.0 parts by weight of methyl methacrylate (MMA), 47.3 parts by weight of toluene, and 0.05 part by mass of tris(2,4-di-tert-butylphenyl)phosphite, and the temperature was raised to 105°C while passing nitrogen through.
[0108] As an initial initiator, a solution consisting of 0.58 parts by weight of toluene and 0.15 parts by weight of t-amyl peroxy isononanoate (manufactured by Arkema Yoshitomi Co., Ltd., Luperox (registered trademark) 570) was dropped over 9 minutes, while solution polymerization was performed at 105 ° C. to 110 ° C. Then, 11 minutes later, a solution consisting of 0.58 parts by weight of toluene and 0.15 parts by weight of t-amyl peroxy isononanoate (manufactured by Arkema Yoshitomi Co., Ltd., Luperox (registered trademark) 570) was dropped over 180 minutes as a dropping initiator. In addition, simultaneously with the dropping initiator injection, a solution consisting of 6.2 parts by weight of 2-(hydroxymethyl) methyl acrylate (RHMA) and 20.8 parts by weight of methyl methacrylate (MMA) was dropped over 180 minutes, while solution polymerization was performed at 105 ° C. to 110 ° C., and further aging was performed over 100 minutes.
[0109] To the obtained polymerization solution, a solution consisting of 0.83 parts by weight of toluene and 0.15 parts by weight of stearyl phosphate (Phoslex A-18, manufactured by Sakai Chemical Industry Co., Ltd.) was added as a catalyst for the cyclization condensation reaction (cyclization catalyst), and the cyclization condensation reaction to form a lactone ring structure was allowed to proceed for 2.0 hours under reflux at approximately 90°C to 110°C.
[0110] Next, the obtained polymerization solution was passed through a multi-tube heat exchanger maintained at 240°C to complete the cyclization condensation reaction, and then introduced into a vent-type screw twin-screw extruder (L / D=52) with a leaf disk-type polymer filter (filtration accuracy 5μm) at the tip at a processing rate of 90 parts by weight / hour in terms of resin amount to devolatilize the polymerization solution. The number of rear vents of the vent-type screw twin-screw extruder used was 1, and the number of fore vents was 4 (referred to as the first, second, third, and fourth vents from the upstream side), the barrel temperature was 240°C, and the degree of vacuum was 13.3 to 400hPa (10 to 300mmHg). During devolatilization, ion-exchanged water was introduced from behind the first and third vents at a rate of 1.3 parts by weight / hour, and a solution of an antioxidant prepared separately was introduced from behind the third vent at a rate of 0.6 parts by weight / hour. As the antioxidant solution, a solution in which 1.0 part by weight of two types of antioxidants (Irganox 1010 manufactured by BASF Japan and Adeka STAB AO-412S manufactured by ADEKA) was dissolved in 30.4 parts by weight of toluene was used.
[0111] The resulting resin pellets (A2) had a weight average molecular weight of 71,000, a molecular weight distribution of 2.0, a glass transition temperature of 131° C., and a melt flow rate of 5.4. (Production Example 3 [Acrylic Resin (A3)]) A reaction vessel equipped with a stirrer, a temperature sensor, a cooling tube, a nitrogen inlet tube and a dropping pump was charged with 8.1 parts by weight of N-phenylmaleimide (PMI), 1.8 parts by weight of N-cyclohexylmaleimide (CHMI), 32.8 parts by weight of methyl methacrylate (MMA), 55.0 parts by weight of toluene and 0.01 parts by weight of n-dodecyl mercaptan (n-DM). When charging, PMI and CHMI were each made into a toluene solution with a concentration of 30% in a preparation tank that had been heated to 75°C in advance. While stirring the mixture charged in the reaction vessel, the inside of the reaction vessel was replaced with nitrogen and the temperature was raised to 100°C. 0.02 parts by weight of t-butylperoxyisopropyl carbonate was added as a polymerization initiator into the reaction vessel to initiate the reaction, and a dripping solution consisting of 0.02 parts by weight of t-butylperoxyisopropyl carbonate and 0.10 parts by weight of toluene, which had been prepared in advance, and 2.2 parts by weight of styrene (St) were dripped from each dripping funnel at a uniform rate over 4 hours to conduct polymerization under reflux. After the dripping was completed, the polymerization was continued by continuing to heat for another 3 hours or more. The obtained polymerization solution was passed through a multi-tube heat exchanger maintained at 240°C, and then introduced into a vent-type screw twin-screw extruder (L / D=44.5) at a processing rate of 90 parts by weight / hour in terms of the amount of resin, and the polymerization solution was degassed. The vent-type twin-screw extruder used had one rear vent and four fore vents (referred to as the first, second, third, and fourth vents from the upstream side), the barrel temperature was 290°C, and the degree of vacuum was 13.3 to 800 hPa (10 to 600 mmHg). During devolatilization, ion-exchanged water was fed from behind the first, second, and third vents at a feeding rate of 1.3 parts by weight / hour.
[0112] The resulting resin pellets (A3) had a weight average molecular weight of 190,000, a molecular weight distribution of 2.4, and a glass transition temperature of 140°C. Example 1 70 parts by weight of the resin obtained in Production Example 1, 20 parts by weight of a styrene-acrylonitrile copolymer (styrene / acrylonitrile ratio is 73% by weight / 27% by weight, weight average molecular weight is 190,000), and 10 parts by weight of E-glass chopped strand (manufactured by Nittobo, CSF 3PE-332S, fiber length 3 mm, fiber diameter 13 μm) were introduced into a vented screw twin-screw extruder (L / D: 45) and extruded to obtain pellets of a glass fiber reinforced resin composition. The operating conditions of the twin-screw extruder were a barrel temperature of 260°C, a rotation speed of 150 rpm, and a reduced pressure of 13.3 to 400 hPa (10 to 300 mmHg). Example 2 50 parts by weight of the resin obtained in Production Example 1, 40 parts by weight of a styrene-acrylonitrile copolymer (styrene / acrylonitrile ratio is 73% by weight / 27% by weight, weight average molecular weight is 190,000), and 10 parts by weight of E-glass chopped strand (manufactured by Nittobo, CSF 3PE-332S, fiber length 3 mm, fiber diameter 13 μm) were introduced into a vented screw twin-screw extruder (L / D: 45) and extruded to obtain pellets of a glass fiber reinforced resin composition. The operating conditions of the twin-screw extruder were a barrel temperature of 260°C, a rotation speed of 150 rpm, and a reduced pressure of 13.3 to 400 hPa (10 to 300 mmHg). Example 3 65 parts by weight of the resin obtained in Production Example 2, 25 parts by weight of a styrene-acrylonitrile copolymer (styrene / acrylonitrile ratio is 73% by weight / 27% by weight, weight average molecular weight is 190,000), and 10 parts by weight of S glass chopped strand (manufactured by NPO STEKLOPLASTIC, VMP, fiber length 3 mm, fiber diameter 10 μm) were introduced into a vented screw twin-screw extruder (L / D: 45) and extruded to obtain pellets of a glass fiber reinforced resin composition. The operating conditions of the twin-screw extruder were a barrel temperature of 260°C, a rotation speed of 150 rpm, and a reduced pressure of 13.3 to 400 hPa (10 to 300 mmHg). Example 4 70 parts by weight of the resin obtained in Production Example 3, 20 parts by weight of a styrene-acrylonitrile copolymer (styrene / acrylonitrile ratio is 73% by weight / 27% by weight, weight average molecular weight is 190,000), and 10 parts by weight of E-glass chopped strand (manufactured by Nittobo, CSF 3PE-332S, fiber length 3 mm, fiber diameter 13 μm) were introduced into a vented screw twin-screw extruder (L / D: 45) and extruded to obtain pellets of a glass fiber reinforced resin composition. The operating conditions of the twin-screw extruder were a barrel temperature of 270°C, a rotation speed of 150 rpm, and a reduced pressure of 13.3 to 400 hPa (10 to 300 mmHg). Example 5 56 parts by weight of the resin obtained in Production Example 2, 34 parts by weight of a styrene-acrylonitrile copolymer (styrene / acrylonitrile ratio 73% by weight / 27% by weight, weight average molecular weight 190,000), and 10 parts by weight of T-glass (manufactured by Nittobo, fiber length 3 mm, fiber diameter 13 μm) were introduced into a vented screw twin-screw extruder (L / D: 45) and extruded to obtain pellets of a glass fiber reinforced resin composition. The operating conditions of the twin-screw extruder were a barrel temperature of 270°C, a rotation speed of 150 rpm, and a reduced pressure of 13.3 to 400 hPa (10 to 300 mmHg). Comparative Example 1 90 parts by weight of a commercially available methyl methacrylate / methyl acrylate copolymer (Sumitomo Chemical Co., Ltd., Sumipex MM, weight average molecular weight 161,000, molecular weight distribution 2.0, glass transition temperature 110 ° C, melt flow rate 0.6) and 10 parts by weight of E glass chopped strand (Nittobo, CSF 3PE-332S, fiber length 3 mm, fiber diameter 13 μm) were introduced into a vented screw twin-screw extruder (L / D: 45) and extruded to obtain pellets of a glass fiber reinforced resin composition. The operating conditions of the twin-screw extruder were a processing speed of 260 ° C, a rotation speed of 150 rpm, and a vacuum degree of 13.3 to 400 hPa (10 to 300 mmHg). Comparative Example 2 70 parts by weight of a commercially available methyl methacrylate / methyl acrylate copolymer (Sumitomo Chemical Co., Ltd., Sumipex MM, weight average molecular weight 161,000, molecular weight distribution 2.0, glass transition temperature 110 ° C, melt flow rate 0.6), 20 parts by weight of a styrene-acrylonitrile copolymer (styrene / acrylonitrile ratio is 73% by weight / 27% by weight, weight average molecular weight 190,000), and 10 parts by weight of E glass chopped strand (Nittobo, CSF 3PE-332S, fiber length 3 mm, fiber diameter 13 μm) were introduced into a vented screw twin-screw extruder (L / D: 45) and extruded to obtain pellets of a glass fiber reinforced resin composition. The operating conditions of the twin-screw extruder were barrel temperature 260 ° C, rotation speed 150 rpm, and reduced pressure degree 13.3 to 400 hPa (10 to 300 mmHg). Comparative Example 3 18 parts by weight of a commercially available methyl methacrylate / methyl acrylate copolymer (Sumitomo Chemical Co., Ltd., Sumipex MM, weight average molecular weight 161,000, molecular weight distribution 2.0, glass transition temperature 110 ° C, melt flow rate 0.6), 72 parts by weight of a styrene-acrylonitrile copolymer (styrene / acrylonitrile ratio is 73% by weight / 27% by weight, weight average molecular weight 190,000), and 10 parts by weight of E glass chopped strand (Nittobo, CSF 3PE-332S, fiber length 3 mm, fiber diameter 13 μm) were introduced into a vented screw twin-screw extruder (L / D: 45) and extruded to obtain pellets of a glass fiber reinforced resin composition. The operating conditions of the twin-screw extruder were barrel temperature 260 ° C, rotation speed 150 rpm, and reduced pressure degree 13.3 to 400 hPa (10 to 300 mmHg).
[0113] Table 1 shows the evaluation results of each of the examples and comparative examples.
[0114] [Table 1]
Claims
1. A glass fiber reinforced acrylic resin composition comprising a methacrylic resin having a ring structure in its main chain and a fibrous glass filler, Further included are styrene copolymers which are styrene-acrylonitrile copolymers or styrene-acrylonitrile-phenylmaleimide copolymers; A glass fiber reinforced acrylic resin composition, characterized in that the content of the styrene copolymer is 20% by mass or more and 40% by mass or less.
2. 2. The glass fiber reinforced acrylic resin composition according to claim 1, wherein the fibrous glass filler has a primary shape with a fiber diameter of 3 to 25 μm and a fiber length of 0.5 to 10 mm.
3. 3. The glass fiber reinforced acrylic resin composition according to claim 1, wherein the content of the fibrous glass filler is from 2% by mass to 30% by mass.
4. 2. The glass fiber reinforced acrylic resin composition according to claim 1, wherein said methacrylic resin has at least one ring structure selected from the group consisting of cyclic lactone, glutaric anhydride, glutarimide, maleic anhydride and maleimide.
5. 2. The glass fiber reinforced acrylic resin composition according to claim 1, wherein the difference in refractive index between the resin composition containing the methacrylic resin and the styrene copolymer and the fibrous glass filler is 0.03 or less.
6. 2. The glass fiber reinforced acrylic resin composition according to claim 1, wherein a molded article having a thickness of 3 mm has a total light transmittance of 80% or more as measured in accordance with JIS K7361.
Citation Information
Patent Citations
Manufacture of glassfiberrreinforced transparent resin plate
JP1980031822A
Reinforced resin composition
JP1987041248A
Glass-fiber reinforced methacrylic resin composition
JP1989223152A
Preparation of transparent glass-fiber-reinforced thermoplastic resin composition
JP1993331335A
Glass fiber-reinforced methacrylic resin composition
JP2011001527A